Teacher Evaluation - Shinkfield, Anthony J. author. aut Link
X, 400 p.
Keywords: Teacher Evaluation: Guide to Professional Practice is organized around four dominant, interrelated core issues: professional standards, a guide to applying the Joint Committee's Standards, ten alternative models for the evaluation of teacher performance, and an analysis of these selected models. The book draws heavily on research and development conducted by the Federally funded national Center for Research on Educational Accountability and Teacher Evaluation (CREATE). The reader will come to grasp the essence of sound teacher evaluation and will be able to apply its principles, facts, ideas, processes, and procedures. Finally, the book invites and assists school professionals and other readers to examine the latest developments in teacher evaluation.